NewOX - extending the online exXam system to provide automated formative evaluation of student text-based assignments - Keidel, R.; Dreher, Heinz; Conner, E.; Kuster, M. (Kassel University Press, 2008)
A cheat-resistant and foolproof distributed electronic application for summativeassessment of student learning outcomes has been developed and field tested "OnlineeXam" (OX). Good usability experience and feedback features for the students as wellas the lecturers were design goals of the implementation. The field tests showed therobustness of the system in a heterogenic PC pool environment, the ease of use and agood student learning outcome assessment ability (summative assessment) but a lackof a formative impact on the student learning efforts. The incorporation and adoption(for European needs) of a short essay assessment algorithm with a rich user interfaceis proposed.